Features of the poetic works of Bean Shin - Бисенбaевa, Ә. П. (Journal of Oriental Studies, 2018)
This article describes the features of the poetry of Bing Shin, an outstanding representative of Chinese literature, a revolutionary social activity and a poetic voice that spread widely among the people. The author of the article explores the form and looks at the inner depth of the artistic search for the poems of the poet. It also talks about many aspects of children’s poetry, which plays a special role in the work of Bing Shin, analyzes the poet’s ideas in his works devoted to children, artistic values, contradictions and real images in society based on his creations. Taking into account that the poems of the poet are directly connected with the reality of the epoch of that time, the author draws attention to the creative laboratory of the poet - he assesses the ability to show contemporary reality and his skill. The author reviews the content, ideological and artistic values of the poems of the poet, at the same time, the characteristic features of his poetry are considered. Along with this, attention is drawn not only to the thematic systematization of the poems of the poet, but also artistic analysis of the images of children, thereby revealing the features of the poetic creativity of Bing Shin.